Perancangan Desain Antarmuka Aplikasi Mobile DestiGuide Menggunakan Pendekatan User Centered Design - Charles Alexander Ririmasse; I Wayan Santiyasa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Traveling is considered a delightful activity to engage in during leisure time. By employing a UserCentered Design approach, the developed tourism application has successfully delivered a satisfying user experience. This method allowed the developers to focus on users' needs, preferences, and enjoyment while designing and developing the application. The results obtained from the System Usability Scale (SUS) measurement yielded an average score of 77,5 from a total of 20 respondents. This indicates that the application possesses good usability and is relatively easy to navigate for users. Although there is room for further improvement, this conclusion suggests that the application has achieved its main goal of providing a seamless and responsive user experience in searching, exploring, interacting, and obtaining information about various tourist destinations.